Exposition theme girl, Zoe Del Lantis - Haas-Schreiner Photo:::::::::
Exposition theme girl, Zoe Del Lantis, breaking champagne bottle on United Air Lines "Mainliner" (DC-3) to inaugurate new express service to the Pacific Northwest. April 1939 Newspaper clipping about the photo attached to back.